Case Report: A Case of Concomitant Paroxysmal Kinesigenic Dyskinesia and Epilepsy: Can We Treat Two Birds With One Stone? - Geng, Jun-Hong; Zheng, Yang; Li, Quan-Fu; Hou, Qun; Wang, Xiao-Hang; Jiang, Yan (Frontiers in Neurology, 2022)
Background: Paroxysmal kinesigenic dyskinesia (PKD) is characterized by recurrent episodes of movement-induced motor attacks. PKD patients may have concomitant epilepsy. Differentiation between the two disorders and effective control of both diseases remain challenging. Case presentation: We present a Chinese girl with typical manifestations of PKD, who also suffered from generalized tonic-clonic seizures attacks at the same time. Genetic testing confirmed a PRRT2 mutation (c.649dupC). Oxcarbazepine was initially used, but withdrawn due to a hypersensitivity reaction. Levetiracetam was initiated afterwards, which was effective for seizures but failed to control her PKD symptoms. The addition of lacosamide (LCM) completely controlled her PKD symptoms. Conclusion: This is the first case reporting the effectiveness of LCM for concomitant PKD and epilepsy. Our case proposes a novel alternative for such patients who are resistant or cannot tolerate conventional anti-sodium antiepileptics.